An Electromyography (EMG) Analysis After Pre-Cooling Between Male and Female in Recreational Runners - Maghfiroh, Rinna Ainul; Konharn, Kurusart (Universitas Muhammadiyah Surakarta, 2022)
Background: Maintaining internal body temperature is critical for the runner’s performance. The inability to reduce the rising temperature may result in hyperthermia and muscle fatigue. Pre-cooling may lower core temperature, allowing for greater heat storage during exercise and delaying thermally-induced fatigue, as well as increased motor output through decrease electrical activity by cooling the muscles. Furthermore, there have been lack studies that compare electrical activity in muscle between gender differences in response to prolonged exercise after pre-cooling. Objective: The purpose of this study to investigate the changes in electrical activity pre and post cold water immersion (CWI) in male and female recreational runners. Methods: This case involved 2 males and 2 females aged 20 years old who are physically active runner with normal-weight BMI. The outcome was measured using electromyography (EMG) which was carried out every 4 minutes while 1st and 2nd running sessions (16 minutes). Results: Male subjects' electrical activity (mV) decreased significantly between 8 to 16 minutes and 16 to 8 minutes (p=0.04, p<0.05). But not in female subjects (p>0.05). Conclusion: It can be concluded that CWI as pre-cooling had an effect of lowering the electrical activity level in the muscle during running in both genders. Keywords: electromyography, electrical activity, cold water immersion, gender, recreational runner